(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
Changes in the physical, chemical, and mechanical properties of the outer layers of machine parts during wear depend on the chemical composition and structure of the metal, as well as on external friction conditions (pressure, speed, temperature, environment, etc.). This article presents an analysis of scientific results on this.